2019
DOI: 10.1097/aog.0000000000003103
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrics and Gynecology Residents' Perspectives on Wellness

Abstract: Note: The term "resident" in this document refers to both specialty residents and subspecialty fellows. Once the Common Program Requirements are inserted into each set of specialty and subspecialty requirements, the terms "resident" and "fellow" will be used respectively. Where applicable, text in italics describes the underlying philosophy of the requirements in that section. These philosophic statements are not program requirements and are therefore not citable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
1
6
0
3
Order By: Relevance
“…This data is consistent with previous studies that have measured high levels of depression among obstetrics and gynaecology trainees, including a US study which categorised 34.2% of trainees as depressed, a figure well above the quoted lifetime prevalence of depression of approximately 10% . This is also consistent with a recent survey of nearly 5000 American obstetrics and gynaecology trainees, 32% of whom self‐reported depression . This data highlights a concerning trend and the urgent need to address and improve the well‐being of obstetrics and gynaecology trainees.…”
Section: Discussionsupporting
confidence: 90%
“…This data is consistent with previous studies that have measured high levels of depression among obstetrics and gynaecology trainees, including a US study which categorised 34.2% of trainees as depressed, a figure well above the quoted lifetime prevalence of depression of approximately 10% . This is also consistent with a recent survey of nearly 5000 American obstetrics and gynaecology trainees, 32% of whom self‐reported depression . This data highlights a concerning trend and the urgent need to address and improve the well‐being of obstetrics and gynaecology trainees.…”
Section: Discussionsupporting
confidence: 90%
“…Physicians are exposed to tremendous stressors, which can contribute to increased burnout and suicide rates compared with the rest of the population [12]. A national survey of 4999 OBGYN residents found an overall burnout of more than 50%, and nearly one-third admitted to feeling depressed [3]. When it comes to active members of AAGL, in 2017 there was 51% burnout among the respondents [13].…”
Section: Discussionmentioning
confidence: 99%
“…The obstetrics and gynecology (OBGYN) field is no exception. Recent publications have estimated a prevalence of burnout of 45% to 51% among OBGYN physicians and residents [2,3]. Furthermore, residents pursuing fellowships were less likely to be satisfied with their overall career when compared with residents not pursuing fellowships [4].…”
mentioning
confidence: 99%
“…Another recent study of wellness in obstetrics and gynaecology trainees reported a high prevalence of self-identified wellness problems (burnout 51.2%, depression 32.0%, binge drinking 12.6%, drug use 1.1%, and suicide attempt 0.4%). 21 The prevalence of wellness problems increased between the first and second The processes of appointment of prevocational doctors to specialty training programs in Australia and New Zealand now may well select for those who are most vulnerable to burnout and emotional problems. Newer national selection processes -most recently 101 trainee appointments were made from 236 applicants 22 might well mean that rigorous selection criteria favour those with personality characteristics such as perfectionism that make them vulnerable.…”
Section: Distress In Traineesmentioning
confidence: 99%